On mapping moving curves to complex KdV-type equations for the Darboux triad in Euclidean space - Yoon, Dae Won; Yuzbasi, Zuhal Kucukarslan (World Scientific Publ Co Pte Ltd, 2025)
In this paper, we show a class of moving curves for the Darboux triad in Euclidean space that can be mapped onto complex KdV-type equations via the generalization of the Heisenberg ferromagnetic spin chain model. Furthermore, we give an approximation of the relationships with certain standard evolution equations.
Keywords: Space curve; Darboux triad; complex KdV; Euclidean space